The Effect of Long Term use of Glibenclamide on Serum and Urinary Sodium and Potassium Level in Type 2 DM Patients - Ali A. Ali (College of Pharmacy University of Baghdad, 2017)
Long-term use of sulfonylureas including chlorpropamide, is known to potentiate the antidiuretic action of arginine vasopressin (AVP), predisposing to hyponatremia.The present study was designed to evaluate the effect of long term use of glibenclamide on serum and urinary levels of sodium and potassium in Type 2 DM patients in Iraqi DM centers. Ninety eight patients with Type 2 DM who were maintained on different doses of glibenclamide for at least 1 year, attending the centre for Diabetes and Endocrinology in Al-Rusafa, Baghdad, were enrolled in the study, in addition to 15 normal healthy subjects. Patients were allocated into three groups according to the dose of glibenclamide that they received. Blood and urine samples were obtained for evaluation of sodium and potassium levels in these samples by flamephotometry. The results indicated that glibenclamide use resulted in significant elevation in serum levels of sodium and potassium compared to controls, while urinary excretion of these cations was not significantly changed. Stratification of patients according to the dose of glibenclamide revealed that this effect on sodium and potassium was not dose dependent. In conclusion, long term use of glibenclamide impairs normal values of Sodium and potassium independent of the administered dose.    Key words: Glibenclamide, sodium, potassium.